The Serial Mediation Role of Dividend Policy and Capital Structure in Relationship Between Financial Flexibility and Financial Performance - Indrawati, Nur Khusniyah; Jazuli, A Muhamad; Suciati, Ranila; Alfathya, Atmaya Fitra (Fakultas Ekonomi Universitas Kadiri, 2025)
This research aimed to investigate the serial mediation role of dividend policy and capital structure in the relationship between financial flexibility and financial performance. The population of this research consists of property and real estate companies listed on the Indonesia Stock Exchange (IDX) over the 13 years (2010 to 2022). Purposive sampling was used. Based on the determined criteria, six companies were chosen as the sample of this research. Data were collected from financial reports on the IDX website to obtain proxies for each variable used. The data analysis used descriptive and inferential statistics, including Path Analysis and the Sobel test, to examine mediation. The results show that of the 10 proposed hypotheses, four are not significant: financial flexibility does not significantly affect financial performance, either directly or through capital structure, or through the serial mediation of dividend policy and capital structure. Financial flexibility also does not directly affect capital structure. This provides empirical evidence that managing cash holdings alone, as a risk-free asset, is insufficient to mitigate risk and improve financial performance, given that property and real estate companies require large capital expenditures due to their inherent characteristics.